2001
DOI: 10.1128/aem.67.3.1198-1209.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Homoserine Lactone Production Is More Common among Plant-Associated Pseudomonas spp. than among Soilborne Pseudomonas spp

Abstract: A total of 137 soilborne and plant-associated bacterial strains belonging to different Pseudomonas species were tested for their ability to synthesize N-acyl-homoserine lactones (NAHL). Fifty-four strains synthesized NAHL. Interestingly, NAHL production appears to be more common among plant-associated than among soilborne Pseudomonas spp. Indeed, 40% of the analyzed Pseudomonas syringae strains produced NAHL which were identified most often as the short-chain NAHL, N-hexanoyl-L-homoserine lactone, N-(3-oxo-hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(159 citation statements)
references
References 52 publications
6
150
3
Order By: Relevance
“…than in free-living soil Pseudomonas spp. (30). This observation suggests that quorum sensing is important in bacterial relationships with eukaryotes.…”
Section: Introductionmentioning
confidence: 94%
“…than in free-living soil Pseudomonas spp. (30). This observation suggests that quorum sensing is important in bacterial relationships with eukaryotes.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies revealed that quorum sensing by gram-negative bacteria involves N-acyl homoserine lactones (AHLs) that differ in the structures of their N-linked acyl side chains as signal molecules (23,29). AHLs are synthesized by the coupling of homoserine lactone rings from Sadenosylmethionine and acyl chains from the acyl-ACP pool in cells by the enzymes LuxI in Vibrio fischeri (27) and PsyI in P. syringae (12). Because 3-oxoacyl-ACP synthase III correlates with fatty acid biosynthesis, we speculated that orf3 has a critical role in AHL production.…”
mentioning
confidence: 99%
“…It has been reported that the AHL-producing bacteria represent 10-30% of the culturable bacteria in soil and rhizospheric environments (9,10,43,45). In this study, AHL production was observed with 12.6% of the leaf isolates and 9.3% of the root isolates.…”
Section: Discussionmentioning
confidence: 59%